Development of organic production in Ukraine - Radolova, O. (ТДАТУ, 2018)
Ukraine‘s agricultural sector has experienced constant growth in recent years and it is the sector which proved to be resistant to the effects of the economic recession. Ukraine has favourable conditions for organic agriculture. Indeed, mild climate and fertile soils provide the country with perfect opportunities for organic sector development
Keywords: agricultural sector; Ukraine; organic operators; export volumes